New Technologies and Contested Ideologies: The Tagish First Voices Project. - Moore, Patrick; Hennessy, Kate (American Indian Quarterly)
This article presents the authors examination of the discourses of the Tagish Web site team as they formulate an Indigenous language ideology based on traditional values and contemporary responses to language endangerment that contrasts with the approaches of outside agencies. This study is based on the experiences of the authors participating in the Tagish First Voices project and earlier language documentation initiatives. The subject of language ideologies has been a focus of several studies and is especially appropriate for the analysis of the project.